Amazing Young Sports People - Loader, Mandy (United Kingdom Cambridge University Press, 2009)
The Olympics, the Paralympics and the more contemporary extreme action sports, X Games, are the greatest celebrations of international sporting achievement in the world. Each event is carefully described and is followed by the exciting and varied profiles of two young people, both past and present, who have made incredible contributions to the games
Cambridge Experience Readers, previously known as Cambridge Discovery Readers, is an exciting series of original fiction, adapted fiction and factbooks, specifically written for pre-teen and teenage learners of English.
Contents.
Keywords: Language Learning; Reading books; Beginner/Elementary level; Factbook